Donor T Cells Undermine the Protective Effect of DST + anti-CD154 in Transplant Rejection. (July 2018) - Lozano, Marcos Iglesias; Chicco, Maria; Andrew Lee, W.P.; Brandacher, Gerald; Raimondi, Giorgio
Abstract : Transplantation is the treatment of choice for acute end-stage failure in vital organs, but complications caused by long-term immunosuppression remain a major concern for transplant patients. Costimulation blockade (CoB) regimens have emerged as a powerful immunomodulatory strategy, however their efficacy is affected by multiple factors, including still unknown ones. Recently, several reports have highlighted the unexpected capacity of passenger donor lymphocytes to limit the efficacy of tolerogenic therapies. Paradoxically, in addition to possibly contributing to the development of devastating graft versus host disease, they appear to enhance the recipient's anti-graft humoral and cellular responses. Further studies are then necessary to understand their role in different settings of regulation of alloreactivity. In this study we are aiming to assess if T lymphocytes contained in the donor specific transfusion (DST) inoculum used as part of a very promising CoB regimen, impact the regulation of skin transplant rejection. A peri-transplant CoB regimen based on the administration of total splenocytes as DST + anti-CD154 (MR-1) has a profound protective effect on mouse skin allotransplantation. This treatment, however, does not induce long term survival (MST=58 days). When T cell are depleted from the splenocytes used as a source of DST, the beneficial effect reached a statistically significant increase to a MST=105 days. We studied the specific role of CD4 and CD8 T cell of the inoculum by performing two additional transplant groups that received DST with specific depletion of CD4 or CD8 T cell subsets. Surprisingly, the absence of CD8 T lymphocytes induced a remarkable improvement in transplant survival (MST>160 – ongoing), with 65% of the transplants surviving beyond 150 days. On the contrary, the absence of CD4 abrogated the prolongation of survival observed with the total-T cells depletion in the DST pool and brought it back to a value, MST=64, comparable to unmanipulated DST. In ongoing experiments we are aiming to determine if any correlation exists between the presence/absence/type of donor T lymphocytes and the levels of donor specific antibodies (DSA), generation of autoantibodies, or variations in the strength of the direct and indirect alloresponses. Overall, these data reveal the existence of a novel and very important opposing role for donor passenger lymphocytes regarding their contribution to the modulation of recipient's alloimmunity that significantly modifies the efficacy of DST+MR1 based regimens: a deleterious role for donor CD8, and a beneficial one for CD4 T cells. Identification of the specific mechanisms through which these divergent modulations of the anti-donor alloresponse are exerted will be pivotal for the optimization of clinically effective tolerogenic therapies.